Colchicina na indução in vitro de poliploides e efeitos da poliploidização em Mandevillas ornamentais - Leite, Mariana Pelais (Universidade Federal de São Carlos, 2025)
This study investigates the induction of polyploidy in Mandevilla in vitro, utilizing colchicine as a mitotic inhibitor. The main objective is to establish an effective protocol for polyploidization and evaluate its impacts on three genotypes of Mandevilla. Specific objectives include assessing the effects of exposure time to colchicine on the induction of polyploids, as well as the influence of genotype on the success of polyploid plant development. The results demonstrate that colchicine treatment led to significant changes in the morphological and physiological characteristics of Mandevilla, including alterations in leaf size, stomatal density, chlorophyll content, flower color and size, and photosynthetic efficiency. The findings suggest that induced polyploidization may enhance desirable ornamental characteristics. This research highlights the potential of polyploidization as a strategy to increase the ornamental value of Mandevilla and offers insights for future applications in plant breeding.
Colchicine in the in vitro induction of polyploids and the effects of polyploidization in ornamental Mandevillas
Keywords: Micropropagação; Poliploidia; Antimitótico; Apocynaceae; Ornamentais; Micropropagation; Polyploidy; Antimitotic; Ornamentals; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::MELHORAMENTO VEGETAL